Potential and Challenges on Amphibians and Reptiles Research in West Java - Cahyadi, Ganjar; Arifin, Umilaela (Jurnal Biodjati, 2019)
West Java Province has the largest population amongst others in Java, and therefore land conversion rate in the region is increasing. Approximately 40% of forest areas in West Java has been converted between 1990–2015. As a consequence, the number of biodiversity in the region is decreasing, including amphibians and reptiles. These groups play an important role in the food chain of an ecosystem, and are very sensitive to environmental changes. However, comprehensive research on amphibian and reptile species in West Java is suboptimal. Visual Encounter Survey has performed in seven districts in West Java for one month and has recorded 26 amphibian species and 27 reptile species. These species were including Javan endemic species (for example: Fejervarya iskandari, Huia masonii, Limnonectes microdiscus, Megophrys montana, and Microhyla achatina), introduced species (Calotes versicolor), and species with a new distribution record (Leptophryne borbonica and Kalophrynus minusculus). In addition, cryptic species (Genus Leptophryne and Cyrtodactylus), which are interesting for further studies, were observed. This study has demonstrated that the potential of a comprehensive study of amphibian and reptile species in West Java is great. Apart from this, conserving the biodiversity in the region also challenging due to the high rate in land conversion